Ultra-precision machining of a large amplitude sinusoidal ring surface based on a slow tool servo - Ji, Shijun (Strojniški vestnik, 2016)
A sinusoidal ring surface with a large size, amplitudes in the macro-level, sub-micrometre form accuracy and nanometre surface roughness plays an important role in modern optical systems and precision calibration, but it is difficult to fabricate with traditional cutting methods. A sinusoidal ring surface with a submillimetre amplitude, machined using a slow tool servo (STS) assisted by single-point diamond turning (SPDT) is presented in this paper. The kinematic characteristic of machine axes is analysed to assess the feasibility of the turning process. The tool path generation, tool geometry optimization, and tool radius compensation are investigated for fabrication of the desired surface. A fabricating experiment of a 0.4 mm amplitude sinusoidal ring surface is performed, and the surface profile is measured with a Talysurf PGI 1240, a measurement system for the small to medium sized aspheric optics. After dealing with original measured curves, a form accuracy 0.274 microm in peak-to-valley error (PV) and surface roughness 7.5 nm in Ra are obtained for the machined surface, and it can be seen that STS can be used for machining of a large amplitude sinusoidal ring surface.
Keywords: kinematične lastnosti; sinusoidna površina obroča; ultranatančna obdelava